The Roles of Archive Institution on Indonesia Public Information Disclosure In Digital Era - Okky Rizkyantha (Institut Agama Islam Negeri Salatiga, 2017)
Disclosure of Public Information Policy is a form of government awareness regarding the importance of information in determining policy. Disclosure of this information is intended to provide openness for people to take part and supervise the government and institutional policy. Archives institution is known as one of the managers of information which has primary task is to store various important recordings to be used appropriately. This paper aims to analyze the role of archive institution in public information disclosure in Indonesia, and its conduct regarding it. To bridge the needs of the user and archival institutions, it must preset fast and efficient archive service. Act no. 43 of 2007 on Archive is one proof of the role of archive institutions in the digital era. Many laws govern the freedom of information of a person, in terms of security, privacy, and information dissemination. Electronic archive service It is expected to facilitate accesses, and it is also a form of the archive’s participation in the Public Information. Although in implementation, there are many issues that archives should face in opening access and disseminating information to the public.